The Picker Patient Experience Questionnaire: development and validation using data from in-patient surveys in five countries. - Jenkinson, C; Coulter, A; Bruster, S (2002)
OBJECTIVE: The purpose of this study was to develop and test a core set of questions to measure patients' experiences of in-patient care. Questions were selected from the bank of items developed for use in in-patient surveys undertaken by the Picker Institute for the purposes of assessing the quality of care. DESIGN: The data reported here come from surveys of patients who had attended acute care hospitals in five countries: the United Kingdom, Germany, Sweden, Switzerland, and the USA. Questionnaires were mailed to patients' homes within 1 month of discharge, either to all patients, or to a random sample, discharged during a specified period. SAMPLE: A total of 62 925 questionnaires were returned, with response rates of 65% (UK), 74% (Germany), 63% (Sweden), 52% (Switzerland), and 46% (USA). RESULTS: Fifteen items were selected from the bank of questions included in the Picker in-patient questionnaires. These items have a high degree of face validity and when summed to an index they show a high degree of construct validity and internal reliability consistency. DISCUSSION: Fifteen items derived from the longer form Picker in-patient survey have been found to provide a meaningful picture of patient experiences of health care, and constitute the 15-item Picker Patient Experience Questionnaire. These questions comprise a core set that should be measured in all in-patient facility surveys. The Picker Patient Experience Questionnaire represents a step forward in the measurement of patient experience as it provides a core set of questions around which further optional modules may be added. Scores are easy to interpret and actionable. CONCLUSION: This small set of questions could be incorporated into in-patient surveys in different settings, enabling the comparison of hospital performance and the establishment of national or international benchmarks.